Freud's mistress [large type] : a novel - Mack, Karen (Thorndike Press, 2013)
Vienna Minna Bernays, an overeducated lady's companion with a sharp wit, is abruptly fired, yet again. On the street and out of options, she turns to her sister, Martha, for help. Martha has her own problems with six young children and an absent, disinterested husband -- Sigmund Freud, a struggling professor. Curious, engaging, and passionate Minna is fascinated by Freud's work, and they soon embark on what is at first simply an intellectual courtship . . .